(untitled) (Agroindustria, Sociedad y Ambiente, 2025)
Anthropic activities such as mining, agroindustrial, agricultural and oil activities, lead to the emission of liquid effluents such as agrochemicals, pesticides, heavy metals, emerging pollutants and hydrocarbons, which contaminate soils and water, affecting vegetation, microbiota and are a risk factor for human health, so the objective of this review was to determine the causes of contamination by chemical agents and its consequences in the Latin American context. For this purpose, a search for information was carried out in 240 articles published in scientific databases such as Scopus, Scielo, Latindex, Dialnet, Redalyc and Google Scholar, of which 40 were selected that are related to problems of soil and water contamination by anthropic activities in Latin America, with emphasis on the determination of the activity that produces the pollutant, the type of chemical agent and the impact caused on the ecosystem. The results reveal that in the region there is inadequate control for the reduction of chemical pollutants, which is evidenced by an alarming increase in the levels of contamination of water sources, rivers and lakes, as well as fertile soils, resulting in a reduced availability of drinking water, degradation of soils suitable for agricultural production and increased risks of public health problems due to the presence of heavy metals and agrochemicals in water and soil.